Peran Pemuda dalam Mendukung E-Government di Era Pemerintahan Berbasis Digital 5.0 - Umiyati Haris; Syahrabudin Husein Enala; Syahruddin; Nurjalal (Papsel Journal of Humanities and Policy, 2024)
This research examines the role of youth in supporting e-government in the era of digital-based government 5.0, highlighting how the younger generation can be the main agent in the digital transformation of government. In this context, youth not only act as users of technology, but also as developers of innovations that support the efficiency, transparency, and responsiveness of public services. Secondary data collected through document searches of literature, journal articles, government reports, and other official documents form the basis of this research analysis. The descriptive-analytical qualitative method is used to describe and criticise various aspects of the role of youth in e-government. Case studies such as "LAPOR!" and "Qlue," as well as hackathon initiatives, show how youth directly contribute to the development of digital solutions. In addition, their participation in e-participation platforms such as "Musrenbang Online" shows active engagement in technology-based decision-making processes. Youth also play a role in digital literacy campaigns, helping less tech-savvy communities to utilise e-government services. Involvement in advocacy and research further underlines the potential of youth as a source of innovative ideas and solutions. The results of this study confirm that the contribution of youth in supporting e-government is significant and covers various aspects, from technology development, participation in policy processes, to education and advocacy. Thus, youth are the main key in accelerating the digital transformation of government, ensuring that technology can be maximally utilised to improve the quality of public services and meet the needs of society in the digital era 5.0. Keywords: Youth, E-Government, Digital 5.0, Digital Transformation